Entanglement of purification in holographic systems - Peng Liu; Yi Ling; Chao Niu; Jian-Pin Wu (Journal of High Energy Physics, 2019)
Abstract The holographic entanglement of purification (EoP) in AdS4 and AdS-RN black hole backgrounds is studied. We develop an algorithm to compute the EoP for bipartite configuration with infinitely long strips. The temperature behavior of EoP is revealed for small, intermediate and large configurations: EoP monotonically increases with the temperature for small configurations; while for intermediate configurations, EoP is configuration-dependent; EoP vanishes for large configurations. Our numerical results verify some important inequalities of EoP, which we also prove geometrically in Poincaré coordinate.